2010
DOI: 10.1111/j.1365-294x.2009.04436.x
|View full text |Cite
|
Sign up to set email alerts
|

Heterothallism inSaccharomyces cerevisiaeisolates from nature: effect ofHOlocus on the mode of reproduction

Abstract: Understanding the evolution of sex and recombination, key factors in the evolution of life, is a major challenge in biology. Studies of reproduction strategies of natural populations are important to complement the theoretical and experimental models. Fungi with both sexual and asexual life cycles are an interesting system for understanding the evolution of sex. In a study of natural populations of yeast Saccharomyces cerevisiae, we found that the isolates are heterothallic, meaning their mating type is stable… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 60 publications
1
29
0
Order By: Relevance
“…In this way, the haploid stage filters out lethal recessive mutations and the subsequent haplo-selfing enables recessive, heterozygous mutations to become homozygous and thus influence the phenotype. Intratetrad mating (automixis) after sporulation will have the same effect (Katz Ezov et al ., 2010). Together, this can improve cellular fitness and adaptability to the environment (Pretorius, 2000).…”
Section: Natural and Artificial Diversitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this way, the haploid stage filters out lethal recessive mutations and the subsequent haplo-selfing enables recessive, heterozygous mutations to become homozygous and thus influence the phenotype. Intratetrad mating (automixis) after sporulation will have the same effect (Katz Ezov et al ., 2010). Together, this can improve cellular fitness and adaptability to the environment (Pretorius, 2000).…”
Section: Natural and Artificial Diversitymentioning
confidence: 99%
“…This is mainly due to the homothallic nature of most industrial and feral yeast strains, making them unsuited for this approach. However, it was recently described that several feral strains show a stable haploid mating type, due to a mutation in the HO endonuclease gene, a gene responsible for mating-type switching (Katz Ezov et al ., 2010), making these strains fit for cell-to-cell mating experiments. In principle, also homothallic strains would be amenable to this approach after genetically disrupting the HO endonuclease gene (van Zyl et al ., 1993; Walker et al ., 2005; Blasco et al ., 2011; Fig 3…”
Section: Natural and Artificial Diversitymentioning
confidence: 99%
“…Genomic data indicate that, despite its benefits, switching also has been lost several other times including in the methylotrophs Kuraishia capsulata and Dekkera bruxellensis (22)(23)(24), and in the Saccharomycetaceae Lachancea kluyveri and Kazachstania africana (29,61). Null alleles of HO are frequent among natural populations of S. cerevisiae (62). Losses of switching may simply reflect life in environments that do not require frequent spore formation for survival or dispersal.…”
Section: Ab Ac Bd CD Ef Eg Fhghmentioning
confidence: 99%
“…Interestingly, different data have shown that several heterothallic S. cerevisiae strains have been isolated from wine and natural sites (21,24). However, the majority of natural isolates of S. cerevisiae are considered able to undergo mating type switching and therefore be homothallic (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…Among the homothallic yeast strains of our study, 12 strains presented at least one inactive copy of the HO gene (date not shown). The mutations found in the HO sequences of S. cerevisiae strains are strong indicators of a full or partial loss of endonuclease Ho function, and yeast cells are unable to switch mating type and to exhibit crossing between neighboring "sister" cells (self-diploidization) (24). On the other hand, due to its complex sexual life cycle, homothallic yeast can eliminate cells with deleterious recessive mutations from the population while generating homozygous diploid cells in which these mutations are not present (26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%